Heat-Killed Lactobacillus paracasei SMB092 Reduces Halitosis by Stimulating the Expression of β-Defensins in Oral Keratinocytes - Won-Ju Kim; Gyubin Jung; Taewook Kim; Jinseon Kim; Byung-Serk Hurh; Hangeun Kim; Do Yu Soung (Microorganisms)
The purpose of this study is to evaluate Lactobacillus paracasei SMB092 as a prophylactic agent for oral pathogens. We examined the physical interaction of SMB092 with a host by identifying the presence of mucus-binding (MuB) protein domains and the capacity of the mucin binding. We determined the role of heat-killed SMB092 in host oral immunity by quantifying the mRNA levels of β-defensins (BDs), Toll-like receptors (TLRs), and their cofactors (CD14/CD36) in normal human oral keratinocytes (HOK-16B cells). To assess the clinically relevant oral health effects of heat-killed SMB092, the growth of Porphyromonas (P.) gingivalis and the production of a volatile sulfur compound (H2S) were also measured in the filtered condition media (FCM) obtained from its cultures with HOK-16B cells. SMB092 possessed 14 putative MuB protein domains and was attached to mucin. Significant amounts of hBD1/2 and TLR2/6 were expressed in heat-killed SMB092-treated HOK-16B cells. The specific neutralization of TLR2 attenuated the expression of hBD1/2 and CD14/CD36. The FCM inhibited the growth of P. gingivalis and the production of H2S. Our data indicate that heat-killed SMB092 may contribute to a healthy oral microbiome as an immune stimulant in the production of BDs via the activation of the TLR2/6 signaling pathway.